Quality of life in women with fibromyalgia - Roshan, Rasol; Shariatpanahi, Seyed Shamsia; Tavoli, Azadeh; Qafori, Zynab; Fathi-Ashtiani, Ali (Archives of Medical Science, 2009)
Introduction: Fibromyalgia is a chronic musculoskeletal syndrome whose main symptom is widespread pain in the body associated with particular tender points, which seriously affects the patient’s functionality and quality of life. This study aimed to evaluate the effect of fibromyalgia on Iranian women’s quality of life and to compare it with that of healthy women. Material and methods: Eighty women with fibromyalgia attending the rheumatology clinic in Tehran and 74 healthy women were entered into the study based on inclusion criteria. SF-36 questionnaire was used to study quality of life. Independent t-test was used to analyze data. Results: Comparing healthy women with fibromyalgic ones showed a significant difference between mean scores of the two groups on subscales of physical functioning, bodily pain, general health, vitality and emotional functioning. However, social functioning and mental health did not show a significant difference between the two groups. Conclusions: The findings of the study show that fibromyalgia negatively affects different aspects of women’s quality of life, especially physical functioning, emotional functioning and general health. So, health authorities should pay more attention to these patients.